Maximizing Benefits From Punctual Ocean Infrastructure: An Ethical Perspective - Whoriskey, Frederick; Barbier, Michele; Mazur, Mackenzie; Hahn, Tobias; Kritzer, Jacob; Vallee, Richard (Frontiers in Marine Science, 2021)
Ethics are becoming a component of best practices in ocean science and observing systems, with maximization of the benefits that stem from investments in ocean science/monitoring being one of the significant ethical issues the science community needs to tackle. Sustained ocean observing systems on issues of global importance are coordinated, internationally sanctioned and making the most out of the resources accorded to them and consequently in a comfortable ethical space. However, huge investments are made globally annually in establishing infrastructure for shorter-term, punctual studies that address other science needs. More could be done to maximize the benefits and impacts of these punctual efforts. Given punctual infrastructure’s small and frequently transient nature, connections to enable sharing will probably be done locally, and both potential additional users and owners of the infrastructure will need to be energetic, receptive and flexible. The accommodation of new uses will have to be balanced against any costs these new activities may impose on the infrastructure. However, such adaptive infrastructures may be the most efficient way to provide the resources needed to identify and monitor emerging or new ocean stressors.